Umunthu, Covid-19 and mental health in Malawi - Kainja, Jimmy; Ndasauka, Yamikani; Mchenga, Martina; Kondowe, Fiskani; M'manga, Chilungamo; Maliwichi, Limbika; Nyamali, Simunye (Elsevier, 2022)
This paper investigates the centrality of Umunthu in mental health conception and treatment in Malawi. Umunthu is an African philosophical worldview which stresses that an individual is human as they relate to others, as in the saying I am because we are. Its communitarian approach contrasts with a predominantly western individualistic worldview; I think therefore I am. There are spelling variations of the word across Bantu languages, including bomoto (Congo), gimuntu (Angola); umunthu (Malawi); vumutu (Mozambique); vumuntu, vhutu (South Africa); humhunu/ubuthosi (Zimbabwe); bumuntu (Tanzania); and umuntu (Uganda). Literature shows that if embraced and advocated for, Umunthu plays a positive and influential role in mainstreaming and dealing with mental health issues in communitarian societies where the Umunthu ideals are part of the social fabric. However, in the case of Covid-19 and mental health in Malawi, the paper argues that Covid-19 preventive measures, particularly self-isolation when Covid-19 positive; maintaining social distance at all times; and reducing the number of people gathered at funerals, challenge Umunthu ideals, which have in the past been crucial in reducing stress, trauma and anxiety. This original paper bases its arguments on empirical data collected in a study conducted in Mangochi, Blantyre, Karonga and Lilongwe. Based on the study's findings, the paper highlights that although Covid-19 preventative measures have been globally embraced, it is also a limiting factor in the quest for mental health in societies with communitarian value systems.
Keywords: Malawi; Mental health; Covid-19; Umunthu; Communitarianism